Automatic TV Broadcast Structuring - Gaël Manson; Sid-Ahmed Berrani (International Journal of Digital Multimedia Broadcasting)
TV broadcast structuring is needed to precisely extract long useful programs. These can be either archived as part of our audio-visual heritage or used to build added-value novel TV services like TVoD or Catch-up-TV. First, the problem of digital TV content structuring is positioned. Related work and existing solutions are deeply and carefully analyzed. This paper presents then DealTV, our fully automatic system. It is based on studying repeated sequences in the TV stream in order to segment it. Segments are then classified using an inductive logic programming-based technique that makes use of the temporal relationships between segments. Metadata are finally used to label and extract programs using simple overlapping-based criteria. Each processing step of DealTV has been separately evaluated in order to carefully analyze its impact on the final results. The system has been proven on a real TV stream to be very effective.